Since `x` is on the right-hand side of the equation, switch the sides
so it is on the left-hand side of the equation.

`5x+8x=24x+11 `

Since `5x` and `8x` are like terms, add `8x` to `5x` to get `13x`
.

`13x=24x+11`

Move all terms not containing `x` to the right-hand side of the
equation.

`-11x=11 `

Divide each term in the equation by `-11` .

`x=-1 `

To solve 24x+11 = 5x+8x arrange all like terms:

`therefore 24x+11 = 13x`

`therefore 24x-13x= -11`

(Take care with symbols when rearranging)

`therefore 11x=-11`

`therefore (11x)/11= -11/11`

`therefore x=-1`

**Ans: from the equation 24x+11=5x+8x x=-1**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.